Inquiry Learning Model in Improving Higher Order Thinking Skills (HOTS) Abilities in Madrasah Ibtidaiyah - Rizal Rifa’i, Muhammad; Setiawati, Ika; Hasim, Zuwati (Institut Studi Islam Muhammadiyah Pacitan, 2025)
Education is an activity to increase person's general knowledge including increasing mastery of theory and skills, deciding and finding problems solutions related to activities in achieving their goals, whether problems in the world of education or everyday life. If formal education in an organization is process of developing abilities in the direction desired by the organization concerned. High Order Thinking Skills (HOTS) are also implemented by the government following still low ranking of the Programme for International Student Assessment (PISA) and Trends in International Mathematics and Science Study (TIMSS) compared to other countries, so that educational standards both in learning process and assessment are further improved by the government through the 2013 curriculum. (Ariyana et al., 2018). According to the revised Bloom's Taxonomy, cognitive processes are divided into two, there are high-level thinking skills or often referred as Higher Order Thinking Skill (HOTS), and low-level thinking skills Lower Order Thinking Skill (LOTS). Low-level thinking skills involve the ability to remember (C1), understand (C2) and apply (C3) while high-level thinking skills involve analysis and synthesis (C4), evaluate (C5), and create or creativity (C6). (Nugroho, 2018). When children have high-level thinking skills in learning process using inquiry that provokes or stimulates students' thinking to develop more analytical, evaluation and creative abilities in children. Students' ability to solve high-level thinking problems can be used by teachers to find out whether students already have high-level thinking skills in learning activities. HOTS-based learning can also provide benefits to students, there are improving achievement, increasing motivation and increasing positive attitudes.